AYAT-AYAT TAJSIM DALAM WACANA PENAFSIRAN AL-QUR'AN - -, Mutmainnah -; Amalih, Ihwan (El-Waroqoh : Jurnal Ushuluddin dan Filsafat, 2025)
This article will reveal the various methods of the interpreters in understanding the tajs?m verses, because in fact, as one of the topics in the Qur'an whose discussion area is related to the Islamic faith, the tajs?m verses continue to be discussed among the interpreters from classical times to contemporary times. Of course, from these discussions, various differences of opinion continue to be born regarding the views of the interpreters in understanding the tajs?m verses. The method used in the study is descriptive analysis with a library research approach which resulted in the conclusion that in understanding the tajs?m verses, the interpreters are divided into three schools of thought. First, the Salaf group or the al-Mufawwidzah school, namely the group that submits the entire meaning of the tajs?m verses to Allah SWT. Second, the Khalaf group or the al-Mu'awwilah school, namely the group that uses the takwil method in understanding the tajs?m verses. Third, the Moderate group or the al-Mutawassitin school, namely the group that chooses the middle way in understanding the tajs?m verses, in the sense that they accept the interpretation of the tajs?m verses if the result is not too contradictory to the scope of the meaning of the word, but if the interpretation of the word is too contradictory to the scope of the meaning of the word in question, they will choose to submit its meaning to Allah SWT as the belief of the Salaf group.